Faktor Risiko Perilaku dan Bitting Activity Anopheles Sp. Dengan Kejadian Malaria di Indonesia: Literature Review - Dwi Fitriani; Mursid Raharjo; martini (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
Malaria is one of the vector-borne diseases that affect the morbidity and mortality of people in the world. Malaria cases recorded in 2017 were 219 million cases worldwide. In 2020, In the southeast Asian region, Indonesia was the highest contributor to confirmed malaria cases at 49.6%, followed by India at 36.4% and Myanmar at 11.5%. The purpose of this study was to determine the risk factors for people's behavior and the activity of biting Anopheles with the incidence of malaria in Indonesia. This research uses the literature review method by analyzing 22 scientific articles related to the research. The results of this study showed that the behavior of not using mosquito nets when sleeping at night, the habit of going out at night, not using mosquito repellent, and not using long clothes are risk factors for malaria events. The peak bites Anopheles at night at 20.00-05.00 WIB and is exofagic. People in endemic areas are expected to be able to use mosquito nets, reduce activities outside the home at night, use mosquito repellent, and use long clothes, especially at night.